The Co–Ti system revisited: About the cubic-to-hexagonal Laves phase transformation and other controversial features of the phase diagram. (December 2019) - Stein, Frank; Merali, Maisam; Watermeyer, Philipp
Abstract: The Co–Ti system is one of the important systems for the development of Co-based superalloys and it is the only binary Co-X system where the characteristic, fine-scaled γ/γ′ microstructures (fcc-Co with fcc L12 -ordered TiCo3 ) can form. Surprisingly, the phase relations and invariant reaction temperatures in the Co-rich part of the system are not very well established and there are fundamental inconsistencies between different versions of the phase diagram. Crucial points such as the type of formation reaction of the γ′ phase TiCo3 from the melt are unclear. The system is not only of high scientific interest because of the presence of the γ/γ' microstructure, but also due to the occurrence of two different, stable polytypes of the Laves phase TiCo2 (hexagonal C36 and cubic C15 type). The phase fields of these two polytypes should be separated by a two-phase field the existence of which however has never been clearly proven. A re-investigation of the Co-rich part of the phase diagram (0–50 at.% Ti) including all invariant reactions as well as the liquidus, solidus, and solvus lines was performed by not only making use of equilibrated alloys but also applying diffusion couples. Graphical abstract: Image 1 Highlights: No two-phase field was found between the C15 and C36 Laves phase fields possibly due to a coherent equilibrium. The invariant reaction between L12 -type TiCo3 (γ′) and the fcc Co solid solution is of eutectic nature. The congruent melting temperature of B2 TiCo is above 1500 °C, which solves some controversy existing in the literature. A revised version of the Co-rich part of the Co–Ti phase diagram is constructed.